Igf2-Reprogrammed Macrophages Ameliorate the Inflammatory Response and Protect Against the Neuroinflammatory Process in Parkinson S Disease Models - Chana-Cuevas, P; Diaz-Espinoza, R (John Wiley and Sons Inc, 2025)
Parkinson s disease (PD) is a neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons in the Substantia Nigra, leading to motor impairment. A hallmark of PD is the presence of misfolded α-synuclein (α-syn) proteins and their neurotoxic accumulations, contributing to neuronal loss. Additionally, the inflammatory response plays a critical role in modulating the neurodegeneration process in PD. Moreover, peripheral macrophages recognize α-syn, triggering chronic inflammation in both the bloodstream and brain tissue, leading to elevated levels of proinflammatory cytokines, as it was observed in PD patient samples. Insulin-like growth factor 2 (IGF2) is a secreted factor with neuroprotective properties in several neurodegenerative disease models. Moreover, IGF2 signaling has been implicated in the cellular reprogramming of macrophages to an anti-inflammatory phenotype through epigenetic changes. Recently, reduced IGF2 levels in both plasma and peripheral blood mononuclear cells (PBMCs) from PD patient samples were reported, suggesting a potential link between IGF2 levels and inflammation. In this study, we investigated the inflammatory profile of PD patients and the effect of IGF2-reprogrammed macrophages in in vitro and in vivo PD models. Here, we report a significant increase in proinflammatory markers in PBMCs from PD patients. IGF2 treatment prevented α-syn-induced pro-inflammatory profile in murine primary macrophages. Notably, IGF2-reprogrammed macrophage treatment significantly reduced motor impairment, α-syn accumulation, and microglial activation in the Substantia Nigra across different stages of disease progression in the PD preclinical model. These findings highlight the immunomodulatory effect of IGF2 on macrophages and its potential therapeutic impact on PD. © 2025 The Author(s). Aging Cell published by Anatomical Society and John Wiley & Sons Ltd.